First records of Scotaena Klug, 1810 species (Hymenoptera, Tiphiidae, Thynninae) in the Brazilian Atlantic Rainforest - Carnimeo, Fernando Henrique [UNESP]; Justino, Cíntia Eleonora Lopes [UNESP]; Noll, Fernando Barbosa [UNESP] (Pensoft Publishers, 2017)
Scotaena is considered a dumping ground genus of the Neotropical thynnine, having both a complicated taxonomy and a poorly known geographical distribution. This work presents the first records of Scotaena decora (Smith, 1859), and Scotaena polistoides Turner, 1910 in 13 areas of the Brazilian Atlantic Rainforest in São Paulo state, Brazil. Both species were previously known only from their type localities, in Amazonia, Brazil and Chaco, Paraguay, respectively. These new records expand the range of distributions of both species to a new biome and contribute to the natural history of the genus.
Keywords: Neotropics; Parasitoid wasps; Semideciduous Atlantic forest